THE ROLE OF THE FOOD AND DRUG SUPERVISORY AGENCY (BPOM) IN MANAGING CIRCULATION OF COSMETICS AND HAZARDOUS FOODS - Andi Najemi; Lilik Purwastuti; Kabib Nawawi (Berumpun: International Journal of Social, Politics, and Humanities, 2019)
In order to overcome currency of dangerous cosmetics, medicines and foods, so that the eforts of the trackling need to be enhenced, from society, government institution and upholder of laws institution which in this case is BPOM. The aim of POM is to discovery, prevent and control products included to protect consuments safety and healthy. BPOM has national and international network linking and also authority of laws and has high professional credibilies. That's why this reaserch was aimed to find out an appropriate of laws strategy that could be taken by BPOM as institute which has authority to ward off and giving law protection for the consuments caused of the accurancy of dangerous cosmetics and food. Based on this research and it's discussion, that is the regulations of cosmetics products must be fulfilled as attached rules regarding of pasal 2 the judgement of BPOM RI no. HK.00.05.4.1745 about cosmetics, the purpose of BPOM Jambi in order to warding off dangerous cosmetics and food currency for healthy, is appliying two stages of control those are pre-market and post-market. As the eforts of post-market control, BPOM continouesly gives education to consuments through communication, information and aducation and also publish public warning to society if it's found dangerous cosmetics and foods, and increas the collaboration with related agency such as official of healthy and tha official of perindag so that the use of dangerous materials could be controlled. The control of cosmetics, medicines and foods (POM) comprehensively covering pre-market nad post-market evaluation and post-market control would be held routine and continously by BPOM. The effort of safety to protect society from currency of danggerous cosmetics and foods, had fulfilled the regulation of mutual rules and or safety and or benefits, and controling activity and safety afforementioned in the case of cismetics and food could be fulfilledz so that there were some eforts non pr ojustitia and pro justitia.